Cell type dependent stability and virulence of a recombinant SARS-CoV-2, and engineering of a propagation deficient RNA replicon to analyze virus RNA synthesis - Wang, Li; Guzman, María; Muñoz-Santos, Diego; Honrubia, Jose Manuel; Ripoll-Gomez, Jorge; Delgado, Rafael; Sola, Isabel; Enjuanes, Luis; Zuñiga, Sonia (Frontiers in Cellular and Infection Microbiology, 2023)
Engineering of reverse genetics systems for newly emerged viruses allows viral genome manipulation, being an essential tool for the study of virus life cycle, virus-host interactions and pathogenesis, as well as for the development of effective antiviral strategies. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emergent human coronavirus that has caused the coronavirus disease (COVID-19) pandemic. The engineering of a full-length infectious cDNA clone and a fluorescent replicon of SARS-CoV-2 Wuhan-Hu-1, using a bacterial artificial chromosome, is reported. Viral growth and genetic stability in eleven cell lines were analyzed, showing that both VeroE6 cells overexpressing transmembrane serin protease 2 (TMPRSS2) and human lung derived cells resulted in the optimization of a cell system to preserve SARS-CoV-2 genetic stability. The recombinant SARS-CoV-2 virus and a point mutant expressing the D614G spike protein variant were virulent in a mouse model. The RNA replicon was propagation-defective, allowing its use in BSL-2 conditions to analyze viral RNA synthesis. The SARS-CoV-2 reverse genetics systems developed constitute a useful tool for studying the molecular biology of the virus, the development of genetically defined vaccines and to establish systems for antiviral compounds screening.